Puck Through Time: Myth, Theatre, and Scenic Reinterpretations in A Midsummer Night’s Dream - Amores Sánchez, Alejandro (Amaltea. Revista de Mitocrítica, 2026)
This article analyzes the figure of Puck from a mythocritical, historical, and performative perspective, examining both his folkloric origins and his reinterpretation in contemporary stage and audiovisual adaptations. Drawing on medieval sources documenting the Anglo-Saxon puca, the study traces the process that transforms this ambiguous being into the dramatic character shaped by Shakespeare in A Midsummer Night’s Dream. The analysis focuses on three interpretations: Michael Hoffman’s film (1999), Tamzin Townsend’s theatrical adaptation (2007), and Julie Taymor’s stage production (2013). The study argues that the myth of Puck is continually reactivated through different performance languages, reflecting broader aesthetic, ideological, and cultural transformations.